Hepatitis B virus genotypes A1 and A2 have distinct replication phenotypes due to polymorphisms in the HBx gene. - Min Zhang; Karim Mouzannar; Zhensheng Zhang; Yuji Teraoka; Jason Piotrowski; Yuji Ishida; Chise Tateno-Mukaidani; Takeshi Saito; Hiromi Abe-Chayama; Kazuaki Chayama; T Jake Liang (PLoS Pathogens)
HBV genotype A has two major subtypes, A1 (commonly in Africa) and A2 (commonly in Europe) with only 4% nucleotide differences. Individuals infected with these two subtypes appear to have different clinical manifestations and virologic features. Whether such a difference results from the virus or host has not been established. Using HBV generated from molecule clones of subtypes A1 and A2 in cell culture (HBVcc), we demonstrate that HBVcc of subtypes A1 and A2 can be passaged in vitro and in vivo and respond equally well to human IFN-α treatment. HBVcc passaged in human liver chimeric mice (HBVmp) infected human hepatocytes more efficiently than that of the original HBVcc. Subtype A2 showed a much higher viral replication level than that of subtype A1. Mechanistic investigations using constructs with chimeric A1/A2 sequences and specific mutations indicated that subtype A2 has an inherently higher replication phenotype due to specific polymorphisms in the HBx gene resulting in amino acid variations. Studies of HBx expression demonstrated that A1 HBx is expressed at a much lower level than that of A2 HBx. Mutagenesis studies identified two HBx amino acid variations responsible for the observed phenotypic difference. Using AlphaFold2, we generated structural models of HBx proteins of A1 and A2. Superposition of the two models reveal that the overall structural motifs are similarly aligned, except for the C-terminal peptides diverging between the A1 and A2 models, possibly explaining their functional difference. In conclusion, using various in vitro and in vivo models, here we show that subtype A2 has an inherently higher replication phenotype due to polymorphisms in HBx that result in possible differences in structure and expression level of the two subtype HBx proteins. This genotypic difference potentially explains the reported clinical differences between the two subtypes as well as providing a previously unrecognized association between viral sequence variations and clinical manifestations of HBV infection in humans.